2011
DOI: 10.2134/agronj2011.0071
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Responses of Corn to Planting Date and Plant Density

Abstract: Corn (Zea mays L.) grain yield is closely related to plant density and is typically maximized in the northern Corn Belt when planting occurs in late April. However, spring rainfall events oft en result in wet soil conditions that delay planting. From 2008 to 2010, experiments were conducted at two locations in southern Minnesota to determine whether the agronomic responses of corn to plant density diff er with planting date. Six plant densities ranging from 38,400 to 107,900 plants ha -1 were evaluated within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
97
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 31 publications
14
97
0
Order By: Relevance
“…However, OP has trended upward over time (Hammer et al 2009), and thus the economically optimum seeding rate commonly differs among hybrids (Van Roekel and Coulter 2011). In other words, the strong reliance of maize crop upon plant population density makes the assessment of hybrid-and site-specific optimum plant population densities imperative.…”
Section: Current Crop Management Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…However, OP has trended upward over time (Hammer et al 2009), and thus the economically optimum seeding rate commonly differs among hybrids (Van Roekel and Coulter 2011). In other words, the strong reliance of maize crop upon plant population density makes the assessment of hybrid-and site-specific optimum plant population densities imperative.…”
Section: Current Crop Management Statusmentioning
confidence: 99%
“…Maize grain yield increased from about 1,500 kg/ha in the early 1900s to 8,500 kg/ha at the beginning of the 2000s in the USA (Boomsma et al 2009;Assefa et al 2012). Despite this spectacular achievement, maize grain yield is closely related to plant population density (Van Roekel and Coulter 2011), and the crop suffers from an agronomic weakness of prime significance, affecting its grain productivity and stability. Modern hybrids (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results showed that the increase of plant density from 70 thousand plants ha -1 to 90 thousand plants ha -1 resulted only in a minimal yield increment (412-1111 kg ha -1 ) but it could considerably increase the risk of production under such ecological and agrotechnical conditions which are inferior to the optimal. In the experiments of Dawadi and Sah (2012), Mohseni (2013) and Roekel and Coulter (2011), the maximum yields were obtained at similar plant densities (60-80 thousand plants ha -1 ), though under different ecological and agrotechnical conditions. The optimum plant density was higher (90 thousand plants ha -1 ) in the experiments of Widdicombe and Thelen (2002), Gozübenli et al (2004) and Lashkari et al (2011).…”
Section: Discussionmentioning
confidence: 87%
“…In the study of Mohseni (2013), the increase of plant density from 60000 plants ha -1 (9.09 t ha -1 ) to 80000 plants ha -1 (11.14 t ha -1 ) resulted in a yield increment. Roekel and Coulter (2011) stated that there is a close relationship between maize yield and plant density. The tested hybrid reached its maximum yield at the plant density of 81700 plants ha -1 .…”
Section: Introductionmentioning
confidence: 99%